2016
DOI: 10.1016/j.celrep.2016.04.053
|View full text |Cite
|
Sign up to set email alerts
|

The Adhesion G Protein-Coupled Receptor GPR56/ADGRG1 Is an Inhibitory Receptor on Human NK Cells

Abstract: Natural killer (NK) cells possess potent cytotoxic mechanisms that need to be tightly controlled. Here, we explored the regulation and function of GPR56/ADGRG1, an adhesion G protein-coupled receptor implicated in developmental processes and expressed distinctively in mature NK cells. Expression of GPR56 was triggered by Hobit (a homolog of Blimp-1 in T cells) and declined upon cell activation. Through studying NK cells from polymicrogyria patients with disease-causing mutations in ADGRG1, encoding GPR56, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 64 publications
8
97
0
Order By: Relevance
“…In brief, cells were harvested by centrifugation at 1,500 rpm for 5 min at 4°C, washed once with ice-cold 1× HBSS, and lysed in 100-µl ice-cold modified cell lysis buffer as described previously (29). Proteins were quantified using Bicinchoninic acid protein assay kit (PIERCE, Rockford, IL, USA) by reading absorbance at 550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, cells were harvested by centrifugation at 1,500 rpm for 5 min at 4°C, washed once with ice-cold 1× HBSS, and lysed in 100-µl ice-cold modified cell lysis buffer as described previously (29). Proteins were quantified using Bicinchoninic acid protein assay kit (PIERCE, Rockford, IL, USA) by reading absorbance at 550 nm.…”
Section: Methodsmentioning
confidence: 99%
“…GPR56 was shown to be expressed by cytotoxic NK and T lymphocytes including CD8 + , CD4 + and gd + T cells (41). For NK cells an inhibitory role for GPR56 in controlling steady state activation by associating with the tetraspanin CD81 was revealed (52). Similar to KLRF1, the role of GPR56 for stimulation-dependent production of cytokines by human CD4 + T cells is unknown and needs to be investigated in further studies.…”
Section: Also the Investigations On Murine Memory T Cells Were Eithementioning
confidence: 99%
“…For example, the aGPCR GPR56/ADGRG1 is involved in cortex development, oligodendrocyte development, muscle cell development, innate immunity, and cancer progression (11)(12)(13)(14)(15)(16)(17). Recent studies have highlighted the role of GPR56 in promoting progression of acute myeloid leukemia (18) and progastrin-dependent colon cancer (19) and suggested that a GPR56 inhibitor would be clinically desirable.…”
mentioning
confidence: 99%